2010
DOI: 10.1038/clpt.2010.206
|View full text |Cite
|
Sign up to set email alerts
|

Microdose Study of 14C-Acetaminophen With Accelerator Mass Spectrometry to Examine Pharmacokinetics of Parent Drug and Metabolites in Healthy Subjects

Abstract: A study of the pharmacokinetics of (14)C-labeled acetaminophen (AAP) was performed in healthy Japanese subjects receiving an oral microdose of the drug. After separation by high-performance liquid chromatography (HPLC), the levels of AAP and its metabolites in the pooled plasma specimens were quantified using accelerator mass spectrometry (AMS). The total body clearance (CL(tot))/bioavailability (F) of AAP was within the variation in the reported values at therapeutic doses, indicating the linearity of AAP pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…In addition, although many comparative studies for various drugs have shown PK linearity between the micro-dose and therapeutic dose [25-28], micro-dosing studies may not always accurately predict the PK parameters at higher therapeutic doses [29-31]. This non-linearity may arise from the non-linear disposition of a drug as well as the saturation of metabolic enzymes or drug transporters [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although many comparative studies for various drugs have shown PK linearity between the micro-dose and therapeutic dose [25-28], micro-dosing studies may not always accurately predict the PK parameters at higher therapeutic doses [29-31]. This non-linearity may arise from the non-linear disposition of a drug as well as the saturation of metabolic enzymes or drug transporters [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In this type of study, a microdose of an investigational drug with a radioactivity in the nCi range is administered to humans, and the highly sensitive technique AMS is used to quantify the low concentrations of total radioactivity and (in combination with HPLC) to produce radiochromatograms for metabolite profiling [50,53,68,69]. However, the costs, size and complexity of AMS will have to be reduced to make wide application possible.…”
Section: Future Perspectivementioning
confidence: 98%
“…A review of these studies was published in 2010. 35 Sugiyama and his colleagues have published a number of papers on the linearity question 32,33,[36][37][38] and have endeavoured to predict using in vitro methods such as K m measurement which drugs might deviate from linearity. 39 A commentary around the issues of linearity and the utility of microdosing has been published by Rowland.…”
Section: Scientic Considerationsmentioning
confidence: 99%